Molecular dynamics approach on intermolecular interaction between n-icosane and gemini surfactant assisted nanoparticles - Shamala Devi Vijayakumar; Junaidi Zakaria; Norida Ridzuan (Petroleum Research, 2022)
Wax molecules tend to aggregate, and form wax solid at low temperature and result in a wax deposition. Chemical wax inhibitors are introduced to prevent wax deposition. However, the performance of chemical wax inhibitors is temperature dependent. Computational method using Molecular Dynamics (MD) simulation is used in this research to investigate how temperature affects wax inhibition using 2,5,8,11 Tetramethyl 6 dodecyn-5,8 Diol Ethoxylate Gemini surfactant (GS) and nanoparticles silicon dioxide (NP1), tin oxide (NP2), and nickel oxide (NP3). Wax-wax interaction of H58⋯H61of n-icosane and wax-solute interaction of hydrogen atom from n-icosane wax and carbonyl oxygen atoms from GS and NPs was investigated via radial distribution function analysis (rdf). The findings revealed that GS/NPs blends have a better chance of wax inhibition than corresponding individuals. Besides that, wax-wax interaction was strongest at 288K, indicating the higher chances of wax formation at low temperature. MD simulation is a promising tool for identifying atoms responsible for the wax formation and inhibition and can be used for chemical wax inhibitor screening for different temperature.